Comparison of International Normalized Ratio Measurement between CoaguChek XS Plus and STA-R Coagulation Analyzers. (24th December 2012) - Hur, Mina; Kim, Hanah; Park, Chul Min; La Gioia, Antonio; Choi, Sang-Gyu; Choi, Ju-Hee; Moon, Hee-Won; Yun, Yeo-Min
Abstract : Background . Point-of-care testing (POCT) coagulometers are increasingly being used in the hospital setting. We investigated whether the prothrombin time international normalized ratio (INR) results by CoaguChek XS Plus (Roche Diagnostics GmbH, Mannheim, Germany) can be used reliably without being confirmed with the INR results by STA-R system (Diagnostica Stago S.A.S, Asnières sur Seine, France). Methods . A total of 118 INR measurements by CoaguChek XS Plus and STA-R were compared using Passing/Bablok regression analysis and Bland-Altman plot. Agreement of the INR measurements was further assessed in relation to dosing decision. Results . The correlation of INR measurements between CoaguChek XS Plus and STA-R was excellent (correlation coefficient = 0.964). The mean difference tended to increase as INR results increased and was 0.25 INR in the therapeutic range (2.0-3.0 INR). The overall agreement was fair to good (kappa = 0.679), and 21/118 (17.8%) INR measurements showed a difference in dosing decision. Conclusion . The positive bias of CoaguChek XS Plus may be obvious even in the therapeutic INR range, and dosing decision based on the CoaguChek XS Plus INR results would be different from that based on the STA-R results. The INR measurements by POCT coagulometers still need to be confirmed with the laboratory INR measurements.